Bottom and Concave Surface Rendering in Image-based Visual Hull - Feng, Jie; Song, Bencong; Zhou, Bingfeng (International Journal of Virtual Reality, 2009)
Bottom and concave shapes on object surface are difficult to reconstruct in image-based visual hull method. In this paper, we propose a simple but efficient method to solve these problems in regular image-based visual hull framework. With the help of a simple image acquiring platform which involves a glass and a mirror, we can capture images of the object from both upper and lower side at the same time. Using these images, silhouette cones necessary for reconstructing the bottom and the concave surfaces could be generated. Therefore the final rendering result of the object can be significantly improved in accuracy and reality, especially in the parts of bottom and concaves.